Menurunkan Frequency Stop Operasional Akibat Problem Dusty di Area CPBL PT Adaro Indonesia dengan Menggunakan Rasio Setting Scada System dan Penambahan Line Additional Spayer serta Automatic Spayer System - Kurniawan, Aries Aditya; Tamjidillah, Mastiadi (Jurnal Teknologi Berkelanjutan, 2024)
PT Adaro Indonesia is a leading energy producer company with a mining and coal business sector. PT Adaro Indonesia through its Coal Processing and Barge Loading (CPBL) division produces 5 types of coal which are differentiated by their CV value. In the process there are several things that cause operational stops, one of which is dust. Dusty is generated from the grinding process in crusher equipment with a total loss time in 2022 of 1951 minutes. Basically, the method used uses the PDCA method (plan, do, check, action). From the PDCA method, 3 root problems were obtained that needed to be resolved. Firstly, the material is dry due to the long dry season and extreme weather conditions, this requires maximizing the work of the sprayer system. The two new methods used are capable of carrying out distribution in accordance with the chemical budget forecast plan. Third, the machine used is modified in such a way as to improve the process of setting chemical doses and reporting automatically using a Scada system. From the results of this improvement, a reduction of 90.2% was obtained with NAB entering the category of quality standards permitted in accordance with PP No. 22 2021.